Global Cortical Atrophy Is Associated with an Unfavorable Outcome in Stroke Patients on Oral Anticoagulation - Kubacka, Marta; Zietz, Annaelle; Schaedelin, Sabine; Polymeris, Alexandros A.; Hert, Lisa; Lieb, Johanna; Wagner, Benjamin; Seiffge, David; Traenka, Christopher; Altersberger, Valerian L.; Dittrich, Tolga; Fladt, Joachim; et al. (Cerebrovascular diseases (Basel, Switzerland), 2023)
Introduction: Measures of cerebral small vessel disease (cSVD), such as white matter hyperintensities (WMH) and cerebral microbleeds (CMB), are associated with an unfavorable clinical course in stroke patients on oral anticoagulation (OAC) for atrial fibrillation (AF). Here, we investigated whether similar findings can be observed for global cortical atrophy (GCA). Methods: Registry-based prospective observational study of 320 patients treated with OAC following AF stroke. Patients underwent magnetic resonance imaging (MRI) allowing assessment of GCA. Using the simplified visual Pasquier scale, the severity of GCA was categorized as follows: 0: no atrophy, 1: mild atrophy; 2: moderate atrophy, and 3: severe atrophy. Using adjusted logistic and Cox regression analysis, we investigated the association of GCA using a composite outcome measure, comprising: (i) recurrent acute ischemic stroke (IS); (ii) intracranial hemorrhage (ICH); and (iii) death. Results: In our time to event analysis after adjusting for potential confounders (i.e., WMH, CMB, age, sex, diabetes, arterial hypertension, coronary heart disease, hyperlipidemia, and antiplatelet use), GCA was associated with an increased risk for the composite outcome in all three degrees of atrophy (grade 1: aHR 3.95, 95% CI 1.34–11.63, p = 0.013; grade 2: aHR 3.89, 95% CI 1.23–12.30, p = 0.021; grade 3: aHR 4.16, 95% CI 1.17–14.84, p = 0.028). Conclusion: GCA was associated with our composite outcome also after adjusting for other cSVD markers (i.e., CMB, WMH) and age, indicating that GCA may potentially serve as a prognostic marker for stroke patients with atrial fibrillation on oral anticoagulation.